Antoni: let's do dinner - Porowski, Antoni; Fox, Mindy (Houghton Mifflin Harcourt, 2021)
"In the follow-up to his New York Times bestseller Antoni in the Kitchen, Queer Eye star Antoni Porowski shares exuberantly easy dinners for every night of the week"--